Assessing the Functional Heterogeneity of Monocytes in Human Septic Shock: a Proof-of-Concept Microfluidic Assay of TNFα Secretion - Llitjos, Jean-François; Bounab, Yacine; Rousseau, Christophe; Dixneuf, Sophie; Rimbault, Blandine; Chiche, Jean-Daniel; Textoris, Julien; Pène, Frédéric; Védrine, Christophe (Frontiers in Immunology, 2021)
Objective: The development of advanced single-cell technologies to decipher inter-cellular heterogeneity enable the dynamic assessment of individual cells behavior over time, overcoming the limitation of traditional assays. Here, we evaluated the feasibility of an advanced microfluidic assay combined to fluorescence microscopy to address the behavior of circulating monocytes from septic shock patients. Methods: Using the proposed microfluidic assay we first investigated the production course of LPS-elicited TNFα by single monocytes (encapsulated within droplets) over time in seven septic shock patients and ten healthy volunteers. Simultaneously, we validated the relevance of our results by comparing with flow cytometry assessment of HLA-DR expression and LPS-induced TNFα production by monocytes from the same cohorts of patients. Results: Consistent with the flow cytometry results, the total number of TNFα molecules secreted by encapsulated single monocytes was significantly lower in septic shock patients compared to healthy donors. However, the microfluidic assay revealed heterogeneous individual behavior of monocytes from septic shock patients: TNFα production was dampened at early time points of either 30 minutes or 60 minutes after LPS stimulation. Noteworthy, monocytes from healthy donors and from septic patients exhibited similar phagocytic activities over time. Conclusion: This microfluidic assay may well represent a useful tool to understand the mechanisms of post septic immunosuppression.